Neurological Monitoring and Management for Adult Extracorporeal Membrane Oxygenation Patients: Extracorporeal Life Support Organization Consensus Guidelines - Cho, Sung-Min; Hwang, Jaeho; Chiarini, Giovanni; Amer, Marwa; Antonini, Marta Velia; Barrett, Nicholas; Belohlavek, Jan; Blatt, Jason E; Brodie, Daniel; Dalton, Heidi J; Diaz, Rodrigo; Elhazmi, Alyaa; et al. (ASAIO journal (American Society for Artificial Internal Organs, 2024)
BACKGROUND: Critical care of patients on extracorporeal membrane oxygenation (ECMO) with acute brain injury (ABI) is notable for a lack of high-quality clinical evidence. Here, we offer guidelines for neurological care (neurological monitoring and management) of adults during and after ECMO support. METHODS: These guidelines are based on clinical practice consensus recommendations and scientific statements. We convened an international multidisciplinary consensus panel including 30 clinician-scientists with expertise in ECMO from all chapters of the Extracorporeal Life Support Organization (ELSO). We used a modified Delphi process with three rounds of voting and asked panelists to assess the recommendation levels. RESULTS: We identified five key clinical areas needing guidance: (1) neurological monitoring, (2) post-cannulation early physiological targets and ABI, (3) neurological therapy including medical and surgical intervention, (4) neurological prognostication, and (5) neurological follow-up and outcomes. The consensus produced 30 statements and recommendations regarding key clinical areas. We identified several knowledge gaps to shape future research efforts. CONCLUSIONS: The impact of ABI on morbidity and mortality in ECMO patients is significant. Particularly, early detection and timely intervention are crucial for improving outcomes. These consensus recommendations and scientific statements serve to guide the neurological monitoring and prevention of ABI, and management strategy of ECMO-associated ABI.
Keywords: Critical Care; Extracorporeal Membrane Oxygenation; poranění mozku; monitorování fyziologických funkcí; Consensus; Brain Injuries; mimotělní membránová oxygenace; Adult; dospělí; lidé; Monitoring, Physiologic; Humans; konsensus; péče o pacienty v kritickém stavu